Inhibition mechanism investigation of quercetagetin as a potential tyrosinase inhibitor - Liang, Faliang (Frontiers in Chemistry, 2024)
Tyrosinase is one important rate limiting enzyme in melanin synthesis, directly affecting the melanin synthesis. Quercetagetin is one active ingredient from marigold. Thence, the inhibition effects of quercetagetin against tyrosinase were investigated. The results showed quercetagetin could inhibit tyrosinase activity with IC50 value of 0.19 ± 0.01 mM and the inhibition type was a reversible mixed-type. Results of fluorescence quenching showed quercetagetin could quench tyrosinase fluorescence in static process. CD and 3D fluorescence results showed the interaction of quercetagetin to tyrosinase could change tyrosinase conformation to inhibit activity. Moreover, docking revealed details of quercetagetin’s interactions with tyrosinase.